The Genetics of Pemphigus Vulgaris - Vodo, Dan; Sarig, Ofer; Sprecher, Eli (Frontiers in Medicine, 2018)
Pemphigus vulgaris (PV) is a severe autoimmune blistering disease caused by autoantibodies (Abs) directed against epithelial desmosomal components and leading to disruption of cell-cell adhesion. The exact mechanisms underlying the disease pathogenesis are still unknown and treatment remains limited to immunosuppressive agents, such as corticosteroids, which are associated with potentially serious adverse effects. Ethnic propensity, familial occurrence and autoimmune comorbidity, suggest a genetic component to the pathogenesis of the disease, which, if discovered, could advance our understanding of PV pathogenesis and thereby point to novel therapeutic targets for this life-threatening disorder. In this article, we review the evidence for a genetic basis of PV, summarize the different approaches used to investigate susceptibility traits for the disease and describe past and recent discoveries regarding genes associated with PV.